Book Reviews. (1st June 2019) - Grimes, Matt; Murphy, Michael Mary; Hollins, Paul; Stewart, Francis
Exist to Resist, by Matthew Smith (2017) Bristol: Mattko, 224 pp., ISBN: 978-0-99578-320-1 h/bk, £50Vox 80–83, Garry O'Neill (ed.) (2019) Dublin: Hi Tone Books, 416 pp., ISBN 978-0-95694-936-3, p/bk, €40Peepshow, Samantha Bennett (2018) New York: Bloomsbury Academic, 203 pp., ISBN 978-5-0132-186-3, p/bk, £12.99Burning Down the Haus: Punk Rock, Revolution and the Fall of the Berlin Wall, Tim Mohr (2018) Chapel Hill, NC: Algonquin Books, 363 pp., ISBN 978-1-61620-843-1, h/bk, £28.00